Peningkatan Kepuasan Konsumen dengan Model SERVQUAL - Simarmata, Hengki Mangiring Parulian; Simarmata, Poltak Pardamean (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
Excellent service is very important for companies to increase profits and competitive strategies with competitors. This study aims to determine the effect of service quality on customer satisfaction at PT Capella Daihatsu Pematangsiantar. This research is quantitative and descriptive. The sample used was 94 people who were taken by purposive sampling technique. The analytical technique used is to test the validity, reliability test, normality test, t test, to determine the magnitude of the effect used a simple linear regression model. The results of this study indicate a significant positive effect between service quality and customer satisfaction. The magnitude of the effect of service quality is 36.4% on service satisfaction and the remaining 63.6% is influenced by other variables not examined such as customer relationship management and others.